Hambatan Komunikasi Terapeutik Antara Pasien Gangguan Jiwa dengan Perawat, Pendamping Rohani dan Pengelola di Yayasan Al Fajar Berseri - Maya; Wijaya, Lia Nanda (Prisani Cendekia Institute, 2023)
Therapeutic communication in the healing process of patients with mental disorders is very helpful. Nurse skills in therapeutic communication are critical to the success of many psychiatric nursing interventions. In carrying out rehabilitation and healing of patients with mental disorders, Al Fajar Berseri Foundation applies therapeutic communication between patients and nurses, head nurses, spiritual directors and Foundations (managers). In the process of running therapeutic communication, both carried out by nurses, spiritual companions and managers, encountered several obstacles in its implementation. These obstacles require time and adaptation from nurses to mental patients in the institution. The purpose of this study is to explore and reveal the obstacles that occur in the therapeutic communication process that takes place between nurses, spiritual assistants, Foundation managers in patients with mental disorders at Al Fajar Berseri Foundation and how to overcome them. This study used a qualitative approach with constructivitis method. The results stated that therapeutic communication barriers between patients and nurses, spiritual companions and managers at the Al Fajar Berseri Foundation can arise due to a number of factors, including the patient's emotional condition. Variations in the type of communication barriers, namely memory impairments that affect the patient's ability to communicate effectively. The forms of communication barriers with mental patients can range from mild to severe. A patient and empathetic communication approach is key in overcoming barriers to therapeutic communication with mental patients. In addition, it is also important to find the right time and conditions in communicating with patients.